Fitness for life health-optimizing physical education series for senior high school - Porto, Jerome A.; Vargas, Aida A.; Collao, Mia Elaine P. (Quezon City C & E Publishing, Inc, 2016)
"The Health Optimizing Physical Education (HOPE) series for senior high school utilizes experiential learning approaches ageappropriate concepts and interesting activities to help students improve their fitness health and wellbeing as individuals and productive citizens of the society It aims to educate students on fitness sports dance and recreation for life which are essentials to optimum and lifelong health and wellness" -- Preface.
Copyright -- Table of Contents -- Preface -- Unit 1. ABCs of Fitness ; Lesson 1. Fitness and Health ; Lesson 2. Motivation and Stress Management in Physical Fitness ; Lesson 3. Fitness Exercise Protocol ; Lesson 4. Fitness Testing and Assessment -- Unit 2. Aerobic Fitness ; Lesson 5. Aerobics ; Lesson 6. Different Types of Active Physical Activities ; Lesson 7. Getting Started on Aerobic Workouts ; Lesson 8. Warmup Aerobic Activities -- Unit 3. Muscular Fitness ; Lesson 9. Facts about Muscular Fitness ; Lesson 10. FITT Principle Applied to Muscular Exercises ; Lesson 11. Bodyweight Exercises ; Lesson 12. Beginners Workout -- Unit 4. Community Fitness ; Lesson 13. The Fitness Movement in the Philippines ; Lesson 14. Physical Fitness in the Community ; Lesson 15. Organizing and Managing Community Fitness ; Lesson 16. Career Opportunities -- Glossary -- References -- Index.
"K to 12 curriculum compliant"--Cover.
Keywords: Physical fitness for youth -- Philippines; Health education (Secondary)